Assessing the Efficacy of Citrus Aurantifolia Extract on Smear Layer Removal with Scanning Electron Microscope - sharifian, mohammad reza; bolhari, behnam; aminsobhani, mohsen; tavakolian, pardis; monsef esfehani, hamid reza (Iranian Endodontic Journal, 2012)
<span style="font-size: 11pt; color: black; line-height: 99%; font-style: normal; font-family: "Times New Roman","serif"; mso-fareast-font-family: ’Times New Roman’; mso-fareast-language: ZH-CN; mso-bidi-language: FA;">Introduction: The purpose of this study was to determine the effects of citrus aurantifolia (CA) extract on smear layer removal in different parts of root canals. <span style="font-size: 11pt; color: black; line-height: 99%; font-style: normal; font-family: "Times New Roman","serif"; mso-fareast-font-family: ’Times New Roman’; mso-fareast-language: ZH-CN; mso-bidi-language: FA;">Materials and Methods: Thirty-nine single-rooted human teeth were randomly divided into three experimental (n=12) and one control (n=3) groups. Teeth were instrumented using MTwo rotary instruments. Root canals were irrigated with NaOCl during instrumentation. The canals in each group were irrigated with one of the following: completed mixture of citrus aurantifolia extracts, 17% EDTA, and alcoholic extract of CA. Distilled water was used for the control group. The irrigants were left within the canal for 20 minutes, and then rinsed with normal saline solution. Teeth were subsequently split longitudinally into 2 halves, and the canals were examined by a scanning electron-microscope. Cleanliness was evaluated using a five point scoring system. <span style="font-size: 11pt; color: black; line-height: 99%; font-style: normal; font-family: "Times New Roman","serif"; mso-fareast-font-family: ’Times New Roman’; mso-fareast-language: ZH-CN; mso-bidi-language: FA;">Results: Statistical significant difference was found between groups (P<0.05). The smear layer was more effectively removed with 17% EDTA compared to alcoholic CA extract. However, they were both able to remove the smear layer in the coronal segment. Completed CA extract removed more smear layer in coronal and middle parts compared with the alcoholic extract (P=0.001); however, there was no significant difference in the apical part. <span style="font-size: 11pt; color: black; font-style: normal; font-family: "Times New Roman","serif"; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: FA;">Conclusion<span style="font-size: 11pt; color: black; font-style: normal; font-family: "Times New Roman","serif"; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: FA;">: Both of the alcoholic and completed mixtures of citrus aurantifolia extracts were not able to effectively remove smear layer compared with 17% EDTA during root canal therapy.